2013
DOI: 10.1177/0748233713491812
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory and anti-inflammatory cytokines in adolescents from Southeast Bulgarian cities with different levels of air pollution

Abstract: Epidemiological studies demonstrated that the exposure of different air pollutants including particulate matter (PM) has been related to adverse effect on immune system. Current study was designed to investigate cytokines in blood plasma of adolescent persons continuously exposed to different degrees of ambient air pollutions. Tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), IL-12p40, and IL-10 were chosen as cytokines of proinflammatory and anti-inflammatory immune response. The peripheral venous blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…b p-value for interaction term representing the product of NO 2 exposure and DD of asthma. increased IL10 expression and IL-10 plasma levels in children living in highly polluted areas (Calderon-Garcidueñas et al 2009;Dobreva et al 2015), which is also supported by in vitro studies (Saito et al 2002).…”
Section: Discussionsupporting
confidence: 55%
“…b p-value for interaction term representing the product of NO 2 exposure and DD of asthma. increased IL10 expression and IL-10 plasma levels in children living in highly polluted areas (Calderon-Garcidueñas et al 2009;Dobreva et al 2015), which is also supported by in vitro studies (Saito et al 2002).…”
Section: Discussionsupporting
confidence: 55%
“…The increased level of IL-10 after exposure to air pollutants such as diesel exhaust in the airways of patients with asthma indicates that air pollution may induce subtle changes in airway immunobiology ( Leem et al 2005 ). Furthermore, several studies reported increased IL10 expression and IL-10 plasma levels in children living in highly polluted areas ( Calderon-Garcidueñas et al 2009 ; Dobreva et al 2015 ), which is also supported by in vitro studies ( Saito et al 2002 ).…”
Section: Discussionmentioning
confidence: 52%
“…However, some studies found that high concentration of TNF-α was detrimental as it may induce cell death, while low levels were protective and were believed to participate in normal lung function (Kleinbongard et al, 2011). Dobreva et al (2015) found a low level of serum TNF-α but a high level of IL-10 in adolescents living in highly industrialized cities. Different from our observations, Xu et al (2016) also found that serum TNF-α of mice increased significantly after exposure to PM 2.5 via inhalation.…”
Section: Oxidative Damage and Inflammatory Responsementioning
confidence: 99%